1998
DOI: 10.1007/bf02986389
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine by bio-corrosion of phosphide-rich iron

Abstract: Phosphine is a toxic agent and part of the phosphorus cycle. A hitherto unknown formation mechanism for phosphine in the environment was investigated. When iron samples containing iron phosphide were incubated in corrosive aquatic media affected by microbial metabolites, phosphine was liberated and measured by gas chromatography. Iron liberates phosphine especially in anoxic aquatic media under the influence of sulfide and an acidic pH. A phosphine-forming mechanism is suggested: Phosphate, an impurity of iron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 11 publications
2
41
0
Order By: Relevance
“…Also, MTCI had shown that there was no phosphine or phosphorus-containing species in the gas phase from the steam gasification of poultry litter. 4 This also agreed with the explanation given by Glindemann et al 10 for formation of phosphine from the earth crust. Thus, based on the literature, it was assumed that under our catalytic steam gasification conditions no phosphorus component would be present in the product gas.…”
Section: Composition Of Poultry Litter-derived Gasification Productssupporting
confidence: 81%
“…Also, MTCI had shown that there was no phosphine or phosphorus-containing species in the gas phase from the steam gasification of poultry litter. 4 This also agreed with the explanation given by Glindemann et al 10 for formation of phosphine from the earth crust. Thus, based on the literature, it was assumed that under our catalytic steam gasification conditions no phosphorus component would be present in the product gas.…”
Section: Composition Of Poultry Litter-derived Gasification Productssupporting
confidence: 81%
“…Therefore, matrix-bound phosphine is a function of the applied digestion method, and does not necessarily refer to the pre-existence of phosphine gas in the matrix, because it could be in the form of solid phosphides. Phosphides, on the other hand, can hydrolyze in biological aquatic media (Glindemann et al, 1998) to form free phosphine gas.…”
Section: Definitions and Generalized Reviewed Methodsmentioning
confidence: 99%
“…But Libert (1927) and Skinner (1968) failed to detect phosphate-reducing bacterial and concluded that evidence for bacterial reduction of phosphate or organically bound phosphorus is still inconclusive. Glindemann et al (1998) noted that PH 3 is also released from corrosion of phosphorus rich metallic iron, and that process can be accelerated by bacteria. Morton et al (2003) measured phosphates, phosphites, and phosphides in environmental samples and concluded that PH 3 formation may be caused by some forms of phosphides.…”
Section: Introductionmentioning
confidence: 97%